Trans-Pacific Partnership Agreement minus one and enhanced criminal penalty for online copyright piracy: Malaysia’s options - Ida Madieha, Abdul Ghani Azmi; Lim, Heng Gee; Tay, Pek San; Sik, Cheng Peng (Kluwer Law International, 2018)
The burgeoning of online piracy enables copyright materials to be routinely downloaded and exchanged for free, without any deliberate intention to infringe copyright. These acts were done for the purpose of sharing and attract no commercial value, and, hence, may not be considered as culpable criminal conduct because of the lack of intention. The Trans-Pacific Partnership Agreement (TPPA) introduces enhanced criminal provisions which are much harsher than the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) with a view to fight online copyright piracy. Even though the United States of America (US) have withdrawn from the Agreement, the other eleven countries are attempting to revive the Agreement, minus the US. The possibility of the Agreement being eventually implemented by the eleven-member countries is still real. This article examines two new criminal provisions introduced by the TPPA. The first is the criminalization of wilful copyright infringement even if carried out on a non-commercial basis. The second is the culpability of aiding and abetting of copyright offences. As these provisions are already in place in US law, reported judgments from the US on corresponding provisions would be examined. The article concludes with choices that Malaysia could consider in the event these two new obligations are implemented.